2002
DOI: 10.1002/jmv.10131
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, isolation, and partial sequence analysis of hepatitis E virus from domestic animals in China

Abstract: Evidence that hepatitis E is zoonotic is accumulating. Serum samples were collected from pigs, cattle, and goats from various regions of China to determine whether they had been infected with hepatitis E virus (HEV). An in-house enzyme immunoassay (EIA) and reverse transcriptase-polymerase chain reaction (RT-PCR) with primers from open reading frame (ORF) 2 were used to detect anti-HEV antibodies and HEV RNA. The mean positivity rates of anti-HEV antibody for pigs and cattle were 78.8% and 6.3% but none of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
124
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(132 citation statements)
references
References 24 publications
(34 reference statements)
4
124
4
Order By: Relevance
“…The infected patient in the current study also had no history of travel to areas endemic for HEV and did not report contact with persons who had travelled to endemic areas or contact with farm pigs or rodents, although there are accumulating lines of evidence that animals may act as natural hosts of HEV (Erker et al, 1999; Hsieh et al, 1999;Huang et al, 2002;Meng et al, 1997Meng et al, , 1998Pina et al, 2000;Wang et al, 2002;Wu et al, 2002). The increasing globalization of food markets and increased overseas travel for business and pleasure have increased the potential of introducing HEV from not only developing countries but also industrialized countries into Japan.…”
mentioning
confidence: 76%
“…The infected patient in the current study also had no history of travel to areas endemic for HEV and did not report contact with persons who had travelled to endemic areas or contact with farm pigs or rodents, although there are accumulating lines of evidence that animals may act as natural hosts of HEV (Erker et al, 1999; Hsieh et al, 1999;Huang et al, 2002;Meng et al, 1997Meng et al, , 1998Pina et al, 2000;Wang et al, 2002;Wu et al, 2002). The increasing globalization of food markets and increased overseas travel for business and pleasure have increased the potential of introducing HEV from not only developing countries but also industrialized countries into Japan.…”
mentioning
confidence: 76%
“…1,15,16 Moreover, partial or complete genomes of HEV were detected in deer, wild boar, mongoose. [17][18][19] Therefore, there should be some HEV animal reservoirs other than swine that cause zoonotic diseases in HEV-endemic areas.…”
Section: Hev As the Sole Member Of The Hepevirus Genus Inmentioning
confidence: 99%
“…Zoonotic spread of HEV has been suggested as human and swine HEV strains are closely related genetically (Erker et al, 1999;Hsieh et al, 1999;Huang et al, 2002;Meng, 2000;Meng et al, 1997Meng et al, , 1998Okamoto et al, 2001;Pina et al, 2000;Wang et al, 2002;Wu et al, 2002), and experimental cross-species infections of swine HEV to non-human primates and that of human HEV to swine have been demonstrated (Erker et al, 1999;Halbur et al, 2001;Meng et al, 1998). In our previous study, we found a high prevalence of swine anti-HEV IgG among Japanese pigs of 2-6 months of age (58 % or 1448/2500) (Takahashi et al, 2003) and identified a pair of Japanese swine and human HEV isolates (swJ13-1 and HE-JA1, respectively) of genotype IV with 99 % identity over the entire genome (Nishizawa et al, 2003).…”
mentioning
confidence: 99%